Highly Efficient Electroreduction of CO2 to C2+ Alcohols on Heterogeneous Dual Active Sites. (22nd July 2020) - Chen, Chunjun; Yan, Xupeng; Liu, Shoujie; Wu, Yahui; Wan, Qiang; Sun, Xiaofu; Zhu, Qinggong; Liu, Huizhen; Ma, Jun; Zheng, Lirong; Wu, Haihong; Han, Buxing
Abstract: Electroreduction of CO2 to liquid fuels such as ethanol and n‐propanol, powered by renewable electricity, offers a promising strategy for controlling the global carbon balance and addressing the need for the storage of intermittent renewable energy. In this work, we discovered that the composite composed of nitrogen‐doped graphene quantum dots (NGQ) on CuO‐derived Cu nanorods (NGQ/Cu‐nr) was an outstanding electrocatalyst for the reduction of CO2 to ethanol and n‐propanol. The Faradaic efficiency (FE) of C2+ alcohols could reach 52.4 % with a total current density of 282.1 mA cm −2 . This is the highest FE for C2+ alcohols with a commercial current density to date. Control experiments and DFT studies show that the NGQ/Cu‐nr could provide dual catalytic active sites and could stabilize the CH2 CHO intermediate to enhance the FE of alcohols significantly through further carbon protonation. The NGQ and Cu‐nr had excellent synergistic effects for accelerating the reduction of CO2 to alcohols. Abstract : Nitrogen‐doped graphene quantum dots (NGQ) on a CuO‐derived‐Cu nanorod (NGQ/Cu‐nr) are used for the electrocatalytic reduction of CO2 to ethanol and n ‐propanol. The Faradaic efficiency of C2+ alcohols could reach 52.4 % with a total current density of 282.1 mA cm −2 . NGQ/Cu‐nr can provide dual active sites and stabilize oxygenic C2 intermediates, resulting in a great improvement in the reduction of CO2 to alcohols.